PANTANAL BASIN: ORIGIN, EVOLUTION AND ENVIRONMENTAL CHANGES - Soares, Paulo César; Soares, Ana Paula; Fiori, Alberto Pio; Carmignani, Luigi; Conceição Paranhos Filho, Antônio; Lastoria, Giancarlo; Maria Facincani, Edna (Boletim Paranaense de Geociências, 2025)
Pantanal basin is a singular environmental and geotectonic entity in central South America. It differs from the extensive tract of depositional systems in the foreland of the Sub-Andean overthrust belt, characterized by the presence of alluvial mega-fans, the most visible feature of these landscapes. The Pantanal basin occupies an entrenched zone in the continental interior and is surrounded by highlands up to 800 m above sea level. Alluvial fans are sourced from the interior. Intraplate tectonic movements and climate changes are active drivers of landscape evolution and human occupation. The fracture basin hypothesis for Andean-related forebulge is reevaluated, together with the role of a transcontinental lineament. Tectonic events and climate changes during the Neogene and Quaternary constituted the driving factors for the source-to-sink movement of sediments, the development of alluvial fans and fluvial mega fan processes. An active regime of tectonic activity submits the Pantanal basin to deformations that significantly modify its landscape at a perceptible speed. Uplift and subsidence, tilting and wrench tectonics, and climatic changes drive landscape evolution. Current tectonic changes impose differential subsidence with drowned landscapes and local uplift zones, where older sediments are eroded. These changes have geometric and kinematic relationships with two active tectonic regional elements: (1) the foreland bulge of the Andes at the back of the Bolivian orocline, moved by reactivation of the Arequipa Massif collision over the South American continental plate border; and (2) the SW‒NE continental lineament zone. This lineament represents a right lateral fracture zone, which has implications for the neotectonic model and is therefore meaningful for understanding the evolution of the Pantanal environment.